Pembangunan Sistem Informasi Tugas Akhir berbasis Website Mahasiswa Jurusan Pemanfaatan Sumberdaya Perikanan dan Kelautan (Studi Kasus : Fakultas Perikanan dan Ilmu Kelautan Universitas Brawijaya) - Adhi Mulhaq; Adam Hendra Brata; Edy Santoso (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Doing the Final Project is an activity of compiling student scientific work on problems in accordance with the competence of the study program that will be pursued by each student as one of the requirements for obtaining a bachelor's degree. In working on the final assignment several stages are needed before a scientific work can be published, such as the stages of submitting topics, selecting supervisors, guidance stages and seminars on proposals and seminars on results. In the Department of Utilization of Fisheries and Marine Resources, Faculty of Fisheries and Marine Sciences, the management of final project services is still manual. So we need a program that can assist in student final assignment management services from the initial submission until the scientific work can be carried out in a results seminar. In addition, services are also needed to be able to monitor the development of scientific work by supervisors. To overcome this problem, research was carried out on the development of the SITA website: Final Project System for the Department of Utilization of Fisheries and Marine Resources, Faculty of Fisheries and Marine Sciences. The development of the system is carried out using the waterfall method approach so that it can minimize errors that might occur. The results of this study found 5 actors who had 46 functional requirements and 1 non-functionality requirement. The built system will be tested using the unit testing method, validation testing and compatibility testing. Testing was carried out using 3 samples in the unit testing section and the entire need for validation testing methods. Compatibility testing using 3 browser devices to find out whether the system can run well or not under different conditions..